2022
DOI: 10.1063/5.0082944
|View full text |Cite
|
Sign up to set email alerts
|

Multi-scale simulation of the adsorption of lithium ion on graphite surface: From quantum Monte Carlo to molecular density functional theory

Abstract: The structure of the double-layer formed at the surface of carbon electrodes is governed by the interactions between the electrode and the electrolyte species. However, carbon is notoriously difficult to simulate accurately, even with well-established methods such as electronic density functional theory and molecular dynamics. Here, we focus on the important case of a lithium ion in contact with the surface of graphite, and we perform a series of reference quantum Monte Carlo calculations that allow us to benc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Carbon materials have been extensively studied, with idealized structures such as pristine carbon walls and carbon nanotubes (CNTs) as well as complex porous structures. It has been observed that liquids in confinement and at interfaces behave significantly different than in bulk. For example, changes in the packing and the rearrangement dynamics within the liquid can be observed. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Carbon materials have been extensively studied, with idealized structures such as pristine carbon walls and carbon nanotubes (CNTs) as well as complex porous structures. It has been observed that liquids in confinement and at interfaces behave significantly different than in bulk. For example, changes in the packing and the rearrangement dynamics within the liquid can be observed. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Approaches based on high-level ab initio calculations will certainly provide an important input towards this direction. 78,79…”
Section: Discussionmentioning
confidence: 99%
“…Approaches based on high-level ab initio calculations will certainly provide an important input towards this direction. 76,77…”
Section: Discussionmentioning
confidence: 99%